2016
DOI: 10.1093/annonc/mdv482
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose fosaprepitant for the prevention of chemotherapy-induced nausea and vomiting associated with moderately emetogenic chemotherapy: results of a randomized, double-blind phase III trial

Abstract: This phase III trial demonstrated that adding a single dose of fosaprepitant to a 5-HT 3 receptor antagonist and corticosteroid in a nonanthracycline and cyclophosphamide-based moderately emetogenic chemotherapy population significantly improved the prevention of chemotherapy-induced nausea and vomiting. The use of this regimen may eliminate the need for multiday antiemetic therapy in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 18 publications
1
64
0
7
Order By: Relevance
“…Furthermore, a consistent clinically meaningful benefit of approximately 10% to 14% with the addition of an NK‐1 RA for patients receiving carboplatin‐based chemotherapy has begun to emerge in the literature 2, 16, 17. In a recent double‐blind, randomized phase 3 study of patients receiving non–AC‐based MEC, 53% of whom received carboplatin‐based chemotherapy, the addition of fosaprepitant to a 5‐HT 3 RA and dexamethasone regimen provided absolute benefits of 10.4% and 10.2% for a CR in the delayed phase and the overall phase, respectively 18. The addition of aprepitant to standard antiemetic regimens yielded absolute benefits of 14% for the measure of no emesis in the overall phase16, 19 and for the CR rate in the overall phase20 in carboplatin‐treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a consistent clinically meaningful benefit of approximately 10% to 14% with the addition of an NK‐1 RA for patients receiving carboplatin‐based chemotherapy has begun to emerge in the literature 2, 16, 17. In a recent double‐blind, randomized phase 3 study of patients receiving non–AC‐based MEC, 53% of whom received carboplatin‐based chemotherapy, the addition of fosaprepitant to a 5‐HT 3 RA and dexamethasone regimen provided absolute benefits of 10.4% and 10.2% for a CR in the delayed phase and the overall phase, respectively 18. The addition of aprepitant to standard antiemetic regimens yielded absolute benefits of 14% for the measure of no emesis in the overall phase16, 19 and for the CR rate in the overall phase20 in carboplatin‐treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that carboplatin, although less emetogenic than cisplatin, is perhaps on the higher end of emetogenic potential within the MEC classification. [21][22][23][24] Several trials and a subset analysis have shown benefit in terms of complete response (CR) in the overall and delayed phases with the addition of a neurokinin-1 (NK1) receptor antagonist (RA) to the 2-drug regimen of a 5-HT3 antagonist and dexamethasone for the prevention of CINV associated with carboplatin-based regimens, thereby affirming the higher emetogenic potential of carboplatin. [21][22][23][24] All of the commercially available NK1 RAs have an FDA-approved indication for MEC chemotherapy, but previous versions of the NCCN Guidelines have supported the addition of an NK1 RA only for select patients receiving MEC with additional CINV risk factors or in those for whom previous therapy with a steroid and 5-HT3 antagonist alone failed.…”
Section: Emetogenicity Of Chemotherapymentioning
confidence: 99%
“…UC San Diego Moores Cancer Center; 22 UCSF Helen Diller Family Comprehensive Cancer Center; 23 St. Jude Children's Research Hospital/The University of Tennessee Health Science Center; 24 Memorial Sloan Kettering Cancer Center; 25 Roswell Park Cancer Institute; 26 University of Michigan Comprehensive Cancer Center; and 27 National Comprehensive Cancer Network.…”
mentioning
confidence: 99%
“…Recently, fosaprepitant was evaluated in a phase III trial that compared a single-day, fosaprepitant-containing antiemetic triplet regimen to a standard 3-day 5-HT 3 RA–dexamethasone regimen in patients treated with MEC [47]. Randomized patients received single-dose (1) fosaprepitant in combination with ondansetron–dexamethasone or (2) ondansetron–dexamethasone on day 1.…”
Section: Introductionmentioning
confidence: 99%